Perspectives of single mothers on the socio-emotional and economic influence of ‘absent fathers’ in child’s life : a case study of rural community in South Africa - Koketso, Matlakala Frans; Calvin, Makhubele Jabulani; Lehlokwe, Sekgale Israel; Mafa, Prudence (Penerbit Universiti Kebangsaan Malaysia, 2019)
The absence of father in child’s life is a challenge in South Africa which is often related to family dysfunction and leads to other social problems. The aim of this study was to explore the perspectives of single mothers on the socio-emotional and economic influence of ‘absent fathers’ in child’s life at a rural community. This study used qualitative approach and multiple case study design. This study constituted of single mothers from a rural community who were purposively sampled. The study used semi-structured interviews to collect data and data was thematically analysed. Absent fathers’ is a serious challenge and its often visible amongst the children on how they interact with the society different from those that come from families with both parents. Children with absent fathers’ experience emotional challenges as they often envy the benefits that the fathers give to their children and that cause emotional glitches to the children. Also, the absence of the father leaves a gap in meeting the basic needs of the children as their single mothers’ struggle to put food on the table on their own and at times as they are having no one to help them, they are not able to meet all the family needs. The phenomenon of absent-fathers still remains a challenging issue in many communities. Children deserted by their fathers irrespective of the reasons advanced have a void in the lives regarding the father-figure with its concomitant benefits and responsibilities.